Nanoalloy Electrocatalysts for Electrochemical Devices - de Sequeira, César Augusto Correia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint covers the most recent advances in nanoalloy electrocatalysts, concerning not only the synthesis, characterization, and modeling, but especially reports of their activity, functionality, durability, and low cost.